Optically induced changes in the band structure of the Weyl charge-density-wave compound - A Crepaldi; M Puppin; D Gosálbez-Martínez; L Moreschini; F Cilento; H Berger; O V Yazyev; M Chergui; M Grioni (JPhys Materials, 2022)
Collective modes are responsible for the emergence of novel quantum phases in topological materials. In the quasi-one dimensional (1D) Weyl semimetal $(TaSe_4)_2I$ , a charge density wave (CDW) opens band gaps at the Weyl points, thus turning the system into an axionic insulator. Melting the CDW would restore the Weyl phase, but 1D fluctuations extend the gapped regime far above the 3D transition temperature ( T $_CDW$ = 263 K), thus preventing the investigation of this topological phase transition with conventional spectroscopic methods. Here we use a non-equilibrium approach: we perturb the CDW phase by photoexcitation, and we monitor the dynamical evolution of the band structure by time- and angle-resolved photoelectron spectroscopy. We find that, upon optical excitation, electrons populate the linearly dispersing states at the Fermi level ( E $_F$ ), and fill the CDW gap. The dynamics of both the charge carrier population and the band gap renormalization (BGR) show a fast component with a characteristic time scale of a few hundreds femtoseconds. However, the BGR also exhibits a second slow component on the µ s time scale. The combination of an ultrafast response and of persistent changes in the spectral weight at E $_F$ , and the resulting sensitivity of the linearly dispersing states to optical excitations, may explain the high performances of $(TaSe_4)_2I$ as a material for broadband infrared photodetectors.